A fluorite-type oxide powder material with a multi-level pore structure and its preparation method and application

By improving the sol-gel method, combining organic solvents and low-temperature treatment, and adding dehydration and carbonization steps, fluorite-type oxide powder material with multi-stage pore structure was prepared, which solved the problem that the prior art was difficult to obtain special properties of fluorite oxides, and achieved material preparation with high porosity and excellent electrochemical properties.

CN118877935BActive Publication Date: 2025-03-21HUAYI NEW ENERGY MATERIALS (SHANGHAI) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410920135.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2025-03-21
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

It is difficult for the prior art to obtain fluorite oxide materials with special physical and chemical properties through improved preparation methods.

Method used

Based on the sol-gel method, combined with specific organic solvents and low-temperature stirring and evaporation treatment, the dehydration and carbonization step before high-temperature calcination is added to prepare fluorite oxide powder material with a multi-stage pore structure.

Benefits of technology

Effectively control particle growth, obtain fluorite oxide powder materials with high porosity and large specific surface area, and show excellent electrochemical properties, and are especially suitable for solid oxide fuel cells and electrolytic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118877935B_ABST
    Figure CN118877935B_ABST
Patent Text Reader

Abstract

The present invention provides a fluorite oxide powder material with a multi-level pore structure, a preparation method thereof and an application thereof; the preparation method of the fluorite oxide powder material of the present invention is based on a sol-gel method, combined with a specific organic solvent and a low-temperature stirring evaporation treatment method, and a step of dehydration and carbonization at a specific temperature is added before high-temperature calcination. It is unexpectedly found that the preparation method of the present invention can effectively control the growth of particles, and a fluorite oxide powder material with a multi-level pore structure is obtained. The powder material has a higher porosity and a larger specific surface area, and has its thermal stability as a high-entropy oxide. In particular, the fluorite oxide powder material with a multi-level pore structure of the present invention exhibits excellent electrochemical performance in a solid oxide fuel cell (SOFC) or solid oxide electrolyzer (SOEC) mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fluorite-type oxide powder material with a multi-level pore structure and a preparation method and application thereof, belonging to the technical field of material chemistry. Background Art

[0002] Fluorite oxides are a class of materials with a special crystal structure; their structure is similar to that of the natural mineral fluorite (CaF2), which is a cubic crystal system based on face-centered close-packing formed by cations, and the tetrahedral interstitial positions are filled by anions. This structure has important application value in the fields of physics and chemistry.

[0003] Fluorite oxide is a typical oxygen ion conductor and can be used as a solid electrolyte material or a support material.

[0004] Oxide materials with fluorite structure include not only common ones such as ZrO2 and UO2, but also a series of high entropy oxides such as (Ce 0.2 La 0.2 Sm 0.2 Nd 0.2 ) 2-δ , cations are evenly distributed in the high-entropy oxide lattice, enhancing the entropy-dominated phase stabilization effect; the unique chemical properties of high-entropy oxides give the material many novel properties.

[0005] Regarding the chemical synthesis method of fluorite-type oxides with high entropy capacity, they can be prepared by precisely controlling the molar ratio of various elements, ensuring the uniform distribution of cationic elements and non-segregated high-entropy fluorite structure.

[0006] The sol-gel method is a common method for synthesizing fluorite-type oxides. The process usually involves dissolving a metal salt precursor in water or an alcohol solution, hydrolyzing it by heating to form a gel, and then drying the gel powder and calcining it. In this process, the properties and structure of the dried gel depend largely on the state of the colloidal substance during solvent evaporation and drying, and the choice of precursor has an important influence on the structure and composition of the solid product.

[0007] How to obtain fluorite oxide with special physical and chemical properties by improving the preparation method is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a method for preparing a fluorite-type oxide powder material with a multi-level pore structure, wherein the preparation method comprises the following steps:

[0009] Step 1): dissolving the first metal salt and the second metal salt and citric acid monohydrate in deionized water to obtain a mixed solution;

[0010] The first metal salt includes ZrO(NO3)2, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and La(NO3)3·6H2O; the second metal salt has a general formula of M(NO3)3·6H2O, wherein the M metal element is selected from any one of Pr, Nd, Sm and Gd;

[0011] In the mixed solution, the concentration of each of the first metal salts is the same and greater than the concentration of any of the second metal salts;

[0012] In the mixed solution, the total metal ion concentration of the first metal salt and the second metal salt is 0.7 to 1.3 mol / L, and the concentration of citric acid monohydrate is 1.5 to 2.5 times the total metal ion concentration;

[0013] Step 2): adding ethylene glycol to the mixed solution, stirring and evaporating at a temperature of 70 to 90° C. for 10 to 15 hours to obtain a colloid;

[0014] The volume ratio of the ethylene glycol to the deionized water in step 1) is 1:15 to 1:20;

[0015] Step 3): dehydrating and carbonizing the colloid obtained in step 2) at a temperature of 150 to 200° C. for 12 to 18 hours;

[0016] Step 4): The dehydrated carbonized solid obtained in step 3) is burned in air at a temperature of 500 to 900° C. for 2 to 6 hours to obtain the fluorite-type oxide powder material.

[0017] In a preferred embodiment of the present application, the chemical formula of the fluorite oxide powder material is (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 G 0.1 O 2-x 、(Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Sm 0.1 O 2-x 、(Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Pr 0.1 O 2-x Or (Zr 0.25 Y 0.25 La 0.25 Ce0.25 ) 0.9 Nd 0.1 O 2-x .

[0018] In a preferred embodiment of the present application, in the step 2), stirring evaporation is performed at a temperature of 80°C; in the step 3), dehydration and carbonization are performed at a temperature of 180°C; and in the step 4), calcination is performed at a temperature of 850°C.

[0019] Another aspect of the present invention provides a fluorite-type oxide powder material with a multi-level pore structure, wherein the fluorite-type oxide powder material is prepared by the above-mentioned preparation method.

[0020] In a preferred embodiment of the present application, the multi-level pore structure characteristics of the fluorite-type oxide powder material include: the multi-level pore structure characteristics of the fluorite-type oxide powder material include: the diameter distribution of macropores is 100nm to 600nm, the diameter distribution of mesopores inside the macropores is 3 to 90nm, and the average particle size of the mesopores is 10 to 75nm;

[0021] Preferably, the diameter distribution of the macropores is 100nm to 300nm, the diameter distribution of the mesopores inside the macropores is 3 to 30nm, the average particle size of the mesopores is 10 to 15nm, and the specific surface area of ​​the mesopores is 0.67 to 13.79m 2 g -1 The pore volume of the mesopores is 0.0006~0.054cc / g.

[0022] In another aspect, the present invention provides the use of the above-mentioned fluorite-type oxide powder material with a multi-level pore structure in the field of catalyst materials, or in the field of adsorbent materials, or in the field of thermal insulation materials, or in the field of ceramic materials, or in the field of battery materials.

[0023] In another aspect, the present invention provides a fuel cell, wherein the electrode material or functional layer material of the fuel cell comprises the above-mentioned fluorite-type oxide powder material with a multi-level pore structure.

[0024] In another aspect, the present invention provides an electrolytic cell, wherein the electrode material or functional layer material of the electrolytic cell comprises the above-mentioned fluorite-type oxide powder material with a multi-level pore structure.

[0025] The preparation method of the fluorite oxide powder material of the present invention is based on the sol-gel method, combined with a specific organic solvent and a low-temperature stirring evaporation treatment method, and a dehydration carbonization step at a specific temperature is added before high-temperature calcination. It is unexpectedly found that the preparation method of the present invention can effectively control the growth of particles, and obtain a fluorite oxide powder material with a multi-level pore structure. The powder material has a higher porosity, a larger specific surface area, and its thermal stability as a high-entropy oxide. In particular, the fluorite oxide powder material with a multi-level pore structure of the present invention shows excellent electrochemical performance in a solid oxide fuel cell (SOFC) or solid oxide electrolyzer (SOEC) mode. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 and Figure 2 The fluorite oxide powder material obtained in Example 1 is respectively a scanning electron microscope photograph at 2.85K and 57.58K (where Figure 2 The sizes of macropores and mesopores are marked);

[0027] Figure 3 The XRD spectrum of the fluorite oxide powder material obtained in Example 1;

[0028] Figure 4 The current-voltage curve of the fluorite oxide powder material obtained in Example 1 as an anode material in a solid oxide fuel cell (SOFC) mode;

[0029] Figure 5 The current-voltage curve of the fluorite oxide powder material obtained in Example 1 as the cathode material in the solid oxide electrolytic cell (SOEC) mode;

[0030] Figure 6 This is a scanning electron microscope photograph of the fluorite oxide powder material obtained in Example 2 at 53.18K (with the sizes of macropores and mesopores marked);

[0031] Figure 7 This is a scanning electron microscope photograph of the fluorite oxide powder material obtained in Example 3 at 47.62K (with the sizes of macropores and mesopores marked);

[0032] Figure 8 This is a scanning electron microscope photograph of the fluorite oxide powder material obtained in Example 4 at 40K (with the sizes of macropores and mesopores marked);

[0033] Fig. 9 This is a scanning electron microscope photograph of the fluorite oxide powder material obtained in Comparative Example 1 at 2.13K;

[0034] Fig.10This is the XRD spectrum of the fluorite oxide powder material obtained in Example 2;

[0035] Fig.11 This is the XRD spectrum of the fluorite oxide powder material obtained in Example 3;

[0036] Fig.12 This is the XRD spectrum of the fluorite oxide powder material obtained in Example 4. DETAILED DESCRIPTION

[0037] The present invention is further described below by way of examples, but the present invention is not limited to these specific embodiments.

[0038] Example 1

[0039] The prepared fluorite-type oxide is a high entropy oxide with the chemical formula (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 G 0.1 O 2-x

[0040] (1) Dissolve 5.6 g (0.0225 mol) of ZrO(NO3)2, 8.6 g (0.0225 mol) of Y(NO3)3·6H2O, 9.7 g (0.0225 mol) of La(NO3)3·6H2O, 9.8 g (0.0225 mol) of Ce(NO3)3·6H2O, 4.5 g (0.01 mol) of Gd(NO3)3·6H2O and 42 g (0.2 mol) of citric acid monohydrate in 100 ml of deionized water, and add 5.3 ml of ethylene glycol.

[0041] (2) Stir at 80°C for 12 h to obtain a jelly-like substance.

[0042] (3) The colloid is dehydrated and carbonized at 180°C for 15 h to obtain a solid powder.

[0043] (4) The solid powder is calcined at 850°C for 2 hours to obtain the oxide powder.

[0044] Example 2

[0045] The prepared fluorite-type oxide is a high entropy oxide with the chemical formula (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Pr 0.1 O 2-x

[0046] (1) Dissolve 5.6 g (0.0225 mol) ZrO(NO3)2, 8.6 g (0.0225 mol) Y(NO3)3·6H2O, 9.7 g (0.0225 mol) La(NO3)3·6H2O, 9.8 g (0.0225 mol) Ce(NO3)3·6H2O, 4.3 g (0.01 mol) Pr(NO3)3·6H2O and 42 g (0.2 mol) citric acid monohydrate in 100 ml of deionized water, and add 5.3 ml of ethylene glycol.

[0047] (2) Stir at 80°C for 12 h to obtain a jelly-like substance.

[0048] (3) The colloid is dehydrated and carbonized at 150°C for 15 h to obtain a solid powder.

[0049] (4) The solid powder is calcined at 700° C. for 4 h to obtain the oxide powder.

[0050] Example 3

[0051] The prepared fluorite-type oxide is a high entropy oxide with the chemical formula (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Nd 0.1 O 2-x

[0052] (1) Dissolve 5.6 g (0.0225 mol) ZrO(NO3)2, 8.6 g (0.0225 mol) Y(NO3)3·6H2O, 9.7 g (0.0225 mol) La(NO3)3·6H2O, 9.8 g (0.0225 mol) Ce(NO3)3·6H2O, 4.3 g (0.01 mol) Nd(NO3)3·6H2O and 42 g (0.2 mol) citric acid monohydrate in 100 ml of deionized water, and add 5.3 ml of ethylene glycol.

[0053] (2) Stir at 80°C for 15 h to obtain a jelly-like substance.

[0054] (3) The colloid is dehydrated and carbonized at 180°C for 18 h to obtain a solid powder.

[0055] (4) The solid powder is calcined at 500° C. for 6 h to obtain the oxide powder.

[0056] Example 4

[0057] The prepared fluorite-type oxide is a high entropy oxide with the chemical formula (Zr 0.25 Y 0.25 La 0.25 Ce0.25 ) 0.9 Sm 0.1 O 2-x

[0058] (1) Dissolve 5.6 g (0.0225 mol) of ZrO(NO3)2, 8.6 g (0.0225 mol) of Y(NO3)3·6H2O, 9.7 g (0.0225 mol) of La(NO3)3·6H2O, 9.8 g (0.0225 mol) of Ce(NO3)3·6H2O, 4.4 g (0.01 mol) of Sm(NO3)3·6H2O and 42 g (0.2 mol) of citric acid monohydrate in 100 ml of deionized water, and add 5.3 ml of ethylene glycol.

[0059] (2) Stir at 80°C for 10 h to obtain a colloid.

[0060] (3) The colloid is dehydrated and carbonized at 180°C for 12 h to obtain a solid powder.

[0061] (4) The solid powder is calcined at 900° C. for 2 h to obtain the oxide powder.

[0062] Comparative Example 1

[0063] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses a conventional solid phase method to prepare high entropy oxide (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 )0.9Gd 0.1 O 2-x Weigh the raw oxide powders of Example 1, mix them, put them into a ball mill, and add an appropriate amount of ethanol as a dispersant. Use a ball mill to mill for 12 hours at 200 rpm to ensure uniform mixing. The ball-milled mixture is dried at 80° C. for 12 hours to remove ethanol and obtain the oxide powder.

[0064] Application Examples

[0065] The materials of Examples 1-4 can be used to make electrode materials or functional layer materials for fuel cells, especially solid oxide fuel cells (SOFCs).

[0066] Anode material

[0067] The preparation method of the anode material is to mix the fluorite oxide powder material obtained in Example 1-4 with an organic additive (α-terpineol and ethyl cellulose) at a mass ratio of 1:1.5 to form a slurry, fully grind on a three-roll grinder for about 2 hours, control the particle size to about 10 μm, and remove excess air bubbles from the slurry with a vacuum defoamer to obtain an anode slurry. The anode slurry is coated on the electrolyte sheet in three layers, and then calcined at 1100° C. in air for 2 hours to form a half-cell.

[0068] Cathode material

[0069] The preparation method of the cathode material is to mix the fluorite oxide powder material obtained in Example 1-4 with an organic additive (α-terpineol and ethyl cellulose) at a mass ratio of 1:1.5 to form a slurry, fully grind on a three-roll grinder for about 2 hours, control the particle size to about 10 μm, and remove excess air bubbles from the slurry with a vacuum defoamer to obtain a cathode slurry. The cathode slurry is coated on the electrolyte sheet in three layers, and then calcined at 1300°C in air for 2 hours to form a half-cell.

[0070] Functional layer materials

[0071] The preparation method of the functional layer material is to mix the fluorite oxide powder material obtained in Example 1-4 with an organic additive (α-terpineol and ethyl cellulose) at a mass ratio of 1:1.5 to form a slurry, fully grind it on a three-roll grinder for about 2 hours, control the particle size to be about 10 μm, remove excess air bubbles from the slurry with a vacuum defoamer, and obtain a functional layer slurry. The functional layer slurry is symmetrically coated on both sides of the electrolyte sheet, and then calcined at 1300° C. in air for 2 hours.

[0072] Performance data

[0073] 1. Scanning Electron Microscope (SEM)

[0074] The morphology and structure were photographed using a Sigma 300 scanning electron microscope with an accelerating voltage of 5 kV and a magnification of 2.85 K and 57.58 K. The scanning electron microscope photos of the fluorite oxide powder material obtained in Example 1 at 2.85 K and 57.58 K are shown in Table 1. Figure 1 and Figure 2 .

[0075] Figure 6 This is a scanning electron microscope photograph of the fluorite oxide powder material obtained in Example 2 at 53.18K. Figure 7 This is a scanning electron microscope photograph of the fluorite oxide powder material obtained in Example 3 at 47.62K. Figure 8 This is a scanning electron microscope photograph of the fluorite oxide powder material obtained in Example 4 at 40K.

[0076] It can be seen from these figures that the oxide powders obtained in Examples 1-4 have a multi-level pore structure in which abundant macropores and mesopores coexist and the large macropores are connected by mesopores.

[0077] Fig. 9 This is a scanning electron microscope photo of the fluorite oxide powder material obtained in Comparative Example 1 at 2.13K. As can be seen from the figure, the surface of the powder material in Comparative Example 1 is smooth and does not have the multi-level pore structure of Example 1 of the present application. It can be seen that the particles of the material in Comparative Example 1 are densified and lose the porous structure.

[0078] 2. XRD diffraction

[0079] The fluorite oxide powder material obtained in Example 1-4 was placed in a carrier. The X-ray diffractometer (ARLEquinox 3500) was set to a scanning angle of 10 to 80 degrees and a scanning time of 5 minutes to obtain its XRD spectrum. The data processing software Jade6.0 was used to smooth the data, subtract the background, search for peaks, retrieve phases, mark characteristic peaks, read characteristic peak information, and compare the peak position with the standard card. The peak that meets a certain standard card contains the corresponding substance.

[0080] The XRD spectrum of the fluorite oxide powder material of Example 1 is shown in Figure 3 Among them, the XRD peak position is completely consistent with the standard card of the main element CeO2, and the powder material is added in molar ratio when synthesizing it, so it is proved that the calcination product obtained in Example 1 is (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 G 0.1 O 2-x .

[0081] The XRD spectrum of the fluorite oxide powder material of Example 2 is shown in Fig.10 , proving that the calcination product obtained in Example 2 is (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Pr 0.1 O 2-x ;

[0082] The XRD spectrum of the fluorite oxide powder material of Example 3 is shown in Fig.11 , proving that the calcination product obtained in Example 3 is (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Nd 0.1O 2-x ;

[0083] The XRD spectrum of the fluorite oxide powder material of Example 4 is shown in Fig.12 , proving that the calcination product obtained in Example 3 is (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Sm 0.1 O 2-x .

[0084] 3. Pore size distribution parameters

[0085] ASAP2460 was used for testing, and the pore size distribution curve of the fluorite oxide powder material obtained in Examples 1-4 was determined by nitrogen low-temperature adsorption method.

[0086] First, the sample is heated and vacuumed to remove impurities adsorbed on the surface. Then it is weighed and placed in liquid nitrogen. At liquid nitrogen temperature, the nitrogen adsorption of the sample is measured at different pre-set pressure points to obtain the adsorption isotherm. The data is then processed by computer to calculate the average pore size and pore size distribution from the adsorption isotherm.

[0087] The measured results show that the diameter distribution of the macropores of the fluorite oxide powder material of Example 1 is 100nm-300nm, the diameter distribution of the mesopores inside the macropores is 3-30nm, the average particle size of the mesopores is 10-15nm, and the specific surface area of ​​the mesopores is 0.67-13.79m 2 g -1 The pore volume of the mesopores is 0.0006~0.054cc / g.

[0088] The pore size distributions of Example 1, Example 2, Example 3 and Example 4 are shown in Table 1 below.

[0089] Table 1

[0090] Example 1 Example 2 Example 3 Example 4 Macropore diameter distribution (nm) 100~300 300~600 100~250 150~300 Mesopore diameter distribution (nm) 3~30 50~90 5~30 5~40 Average particle size of mesopores (nm) 10~15 65~75 10~15 15~25

[0091] 4. Electrochemical performance test

[0092] Figure 4 The current-voltage curve of the fluorite oxide powder material obtained in Example 1 as an anode material in a solid oxide fuel cell (SOFC) mode;

[0093] Figure 5 The current-voltage curve of the fluorite oxide powder material obtained in Example 1 as the cathode material in the solid oxide electrolytic cell (SOEC) mode;

[0094] from Figure 4, Figure 5 It can be seen from the results that in the solid oxide fuel cell (SOFC) mode, the fluorite oxide powder material of Example 1 as the anode material can achieve a high current of 1.26 A·cm at 0.4 V in H2 atmosphere. -2 The current density reaches 0.515W·cm -2 As a cathode material, it also exhibits excellent efficiency in the co-electrolysis of CO2 and H2O in the solid oxide electrolysis cell (SOEC) mode, for example, achieving 1.10 A cm at high temperature 850 °C and 1.5 V. -2 Current density.

[0095] The electrochemical test results of the oxide powder materials obtained in Examples 1-4 and Comparative Example 1 are shown in Table 2 below:

[0096] Table 2

[0097]

[0098]

[0099] It can be seen from Table 2 that Example 1 with a multi-level pore structure has a high SOFC power P max The performance in terms of SOFC current density and SOEC current density is much higher than that of the product without comparative example 1 (material without multi-level pore structure), especially the current density of SOEC is increased by nearly four times. It can be seen from the data in Table 2 that the oxide powder materials with multi-level pore structure obtained in Examples 1-4 show excellent electrochemical performance in the solid oxide fuel cell (SOFC) or solid oxide electrolyzer (SOEC) mode, and improve the efficiency of the cathode for co-electrolysis of CO2 and H2O.

[0100] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0101] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a fluorite-type oxide powder material having a multi-level pore structure, characterized in that: The preparation method comprises the following steps: Step 1): dissolving the first metal salt and the second metal salt and citric acid monohydrate in deionized water to obtain a mixed solution; The first metal salt includes ZrO(NO3)2, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and La(NO3)3·6H2O; the second metal salt has a general formula of M(NO3)3·6H2O, wherein the M metal element is selected from any one of Pr, Nd, Sm and Gd; In the mixed solution, the concentration of each of the first metal salts is the same and greater than the concentration of any of the second metal salts; In the mixed solution, the total metal ion concentration of the first metal salt and the second metal salt is 0.7 to 1.3 mol / L, and the concentration of citric acid monohydrate is 1.5 to 2.5 times the total metal ion concentration; Step 2): adding ethylene glycol to the mixed solution, stirring and evaporating at a temperature of 70 to 90° C. for 10 to 15 hours to obtain a colloid; The volume ratio of the ethylene glycol to the deionized water in step 1) is 1:15 to 1:20; Step 3): dehydrating and carbonizing the colloid obtained in step 2) at a temperature of 150 to 200° C. for 12 to 18 hours; Step 4): the dehydrated carbonized solid obtained in step 3) is burned in air at a temperature of 500 to 900° C. for 2 to 6 hours to obtain the fluorite-type oxide powder material; The chemical formula of the fluorite oxide powder material is (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 G 0.1 O 2-x 、(Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Sm 0.1 O 2-x 、(Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Pr 0.1 O 2-x Or (Zr 0.25 Y 0.25 La 0.25 Ce 0.25 ) 0.9 Nd 0.1 O 2-x .

2. The preparation method according to claim 1, characterized in that: In the step 2), stirring and evaporating is performed at a temperature of 80° C.; In the step 3), dehydration and carbonization are carried out at a temperature of 180°C; In the step 4), calcination is performed at a temperature of 850°C.

3. A fluorite oxide powder material with a multi-level pore structure, characterized in that: The fluorite-type oxide powder material is prepared by the preparation method described in any one of claims 1 to 2.

4. The fluorite type oxide powder material according to claim 3, characterized in that: The multi-level pore structure characteristics of the fluorite oxide powder material include: the diameter distribution of macropores is 100nm-600nm, the diameter distribution of mesopores inside the macropores is 3-90nm, and the average particle size of the mesopores is 10-75nm.

5. The fluorite type oxide powder material according to claim 4, characterized in that: The diameter distribution of the macropores is 100nm-300nm, the diameter distribution of the mesopores inside the macropores is 3-30nm, the average particle size of the mesopores is 10-15nm, and the specific surface area of ​​the mesopores is 0.67-13.79m 2 g -1 The pore volume of the mesopores is 0.0006~0.054cc / g.

6. Application of the fluorite-type oxide powder material with a multi-level pore structure as claimed in any one of claims 3 to 5 in the field of catalyst materials, adsorbent materials, thermal insulation materials, ceramic materials or battery materials.

7. A fuel cell, characterized in that: The electrode material or functional layer material of the fuel cell comprises the fluorite-type oxide powder material with a multi-level pore structure as described in any one of claims 3 to 5.

8. An electrolytic cell, characterized in that: The electrode material or functional layer material of the electrolytic cell comprises the fluorite-type oxide powder material with a multi-level pore structure as described in any one of claims 3 to 5.

Citation Information

Patent Citations

  • Preparation method of rare-earth-based fluorite type high-entropy oxide powder material

    CN108946787A

  • High-temperature heat-insulation fluorite type medium-entropy oxide and preparation method thereof

    CN113248255A